2003
DOI: 10.5194/angeo-21-559-2003
|View full text |Cite
|
Sign up to set email alerts
|

High-latitude observations of impulse-driven ULF pulsations in the ionosphere and on the ground

Abstract: Abstract.We report the simultaneous observation of 1.6-1.7 mHz pulsations in the ionospheric F-region with the CUTLASS bistatic HF radar and an HF Doppler sounder, on the ground with the IMAGE and SAMNET magnetometer arrays, and in the upstream solar wind. CUTLASS was at the time being operated in a special mode optimized for high resolution studies of ULF waves. A novel use is made of the ground returns to detect the ionospheric signature of ULF waves. The pulsations were initiated by a strong, sharp decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…As we mentioned in the Introduction, their generation is commonly attributed to the ion-cyclotron instability in the proton beams reflected from the Earth's bow shock (e.g. Fairfield, 1969;Paschmann et al, 1979). Ponomarenko et al (2002) showed that, through its dependence on solar wind parameters, the signal component most likely originates from the upstream ion-cyclotron instability in reflected proton beams (e.g.…”
Section: Discussion and Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…As we mentioned in the Introduction, their generation is commonly attributed to the ion-cyclotron instability in the proton beams reflected from the Earth's bow shock (e.g. Fairfield, 1969;Paschmann et al, 1979). Ponomarenko et al (2002) showed that, through its dependence on solar wind parameters, the signal component most likely originates from the upstream ion-cyclotron instability in reflected proton beams (e.g.…”
Section: Discussion and Modellingmentioning
confidence: 99%
“…Due to their well-established dependence on solar wind and IMF parameters, it is widely believed that at least some of the daytime band-limited Pc3-4 MHD waves may be generated upstream of the Earth's bow shock by the ion-cyclotron instability in reflected proton beams (Fairfield, 1969;Paschmann et al, 1979;Hoppe and Russell, 1983).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, however, the waves are typically visible as modulations of ground backscatter, as first exploited by Menk et al (2003). developed a new visualistion technique which greatly enhances the ability to identify such modulated ground backscatter returns, and the use of this technique is illustrated in Fig.…”
Section: Externally Driven Wavesmentioning
confidence: 99%
“…The cavity formed by magnetospheric boundaries can be set into oscillation by impulsive driving such as solar wind pressure variation (Menk et al, 2003) or broad band driver such as Kelvin-Helmholtz waves (Chen and Hasegawa, 1974b;Mann et al, 1999). Such oscillations of the magnetospheric waveguide might then cause a local field line to oscillate at its natural frequency where this frequency matches one of the waveguide harmonics Samson et al, 1992;Walker et al, 1992;Wright, 1994;Rickard and Wright, 1994).…”
Section: Discussionmentioning
confidence: 99%